2005
DOI: 10.1097/01.paf.0000188096.28402.c9
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic Deaths Following Treatment for Hypertrophic Obstructive Cardiomyopathy

Abstract: Hypertrophic cardiomyopathy (HCM) is a disease process which results in a large, heavy heart, with hypertrophy of the interventricular septum (IVS) and left ventricle. HCM accounts for a significant number of cases of sudden cardiac death each year, most infamously in young athletes. The prevalence of the disease has increased over the past several years due to advances in clinical diagnosis and molecular genetic studies. Over this same period, new forms of treatment also have emerged. One such treatment is al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…It has been reported that infarcts in the anterior wall of the left ventricle have occurred due to septal ablation therapy (Ruzyllo et al, 2000;Chowdhary et al, 2007), however the frequency of occurrence is not known due to under-reporting of such complications (Batalis et al, 2005). Our study reports that the frequency of DSP termination in the left ventricular anterior wall was 5%.…”
Section: Discussionmentioning
confidence: 64%
“…It has been reported that infarcts in the anterior wall of the left ventricle have occurred due to septal ablation therapy (Ruzyllo et al, 2000;Chowdhary et al, 2007), however the frequency of occurrence is not known due to under-reporting of such complications (Batalis et al, 2005). Our study reports that the frequency of DSP termination in the left ventricular anterior wall was 5%.…”
Section: Discussionmentioning
confidence: 64%
“…Only in a minority of cases (23.6%-category A) is an accurate cause of death determinable with minimal clinical history. This need for detailed clinico-pathological correlation in iatrogenic deaths is also highlighted by the works of several authors, who emphasize the importance of a trustful relationship among the various healthcare providers and the pathologists in the prevention of medical errors and adverse events and a comprehensive clinico-pathological discussion being an essential element for medical auditing and teaching as despite significant progress in diagnostic procedures, autopsy has not always confirmed the clinical diagnosis [7,10,18,19]. We also find that as the number of days of survival between injury and death increases, the greater the need for detailed clinical documentation to ascertain the cause of death.…”
Section: Discussionmentioning
confidence: 96%
“…6) [62,63], which represents a potentially unstable arrhythmogenic substrate which has triggered potentially lethal ventricular tachyarrhythmias in about 10% of ablation patients and raises SD risk in some susceptible individuals [14,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65]. This recognized risk for sustained ventricular tachyarrhythmias occurs largely over the short term [14,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] with reported postprocedural annual event rates of 3% to 5% (Table 2) [64,65]. Based on this consideration, some practitioners have prudently implanted ICDs prophylactically in selected patients following alcohol septal ablation [65].…”
Section: Alcohol Septal Ablationmentioning
confidence: 97%
“…SD risk factors for the selection of HCM patients for primary prevention ICDs BP blood pressure, CMR cardiovascular magnetic resonance, EF ejection fraction, LV left ventricular, LVH left ventricular hypertrophy, NSVT nonsustained ventricular tachycardia, SD sudden death a Gradient ≥50 mmHg at rest b Sustained ventricular tachyarrhythmias have been reported in a significant minority of patients in the short-term following the alcohol septal ablation procedure[14,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] c Wall thickness, ≥30 mm by echocardiography d ≥3 beats at ≥120/min…”
mentioning
confidence: 99%